The relationship between self-regulation and educational performance in students - Sara Sahranavard; Mohamad Reza Miri; Hamid Salehiniya (Wolters Kluwer Medknow Publications, 2018)
INTRODUCTION: Self-regulation and educational performance are among the most important topics to be discussed in schools and universities. The present study aimed to the relationship between self-regulation and educational performance among daughter students of police officers in Birjand City, Iran (public and Payame Noor) in 2017. MATERIALS AND METHODS: This research is a correlational cross-sectional study. In total, 200 female students were selected using random sampling method. The Ryan and Connell's Self-Regulation Questionnaire and Durtaj's educational performance scale were used to collect data. The data were analyzed using the Pearson correlation coefficient. RESULTS: The results showed that there is a significant correlation between self-regulation and educational performance among students of Payame Noor University, whereas it is not significant for public university students. CONCLUSION: We can provide students with effective and useful tips to improve their academic achievement and performance by teaching them self-regulation skills. Therefore, the cornerstone of educational achievement in students should be in that way to achieve the desired educational performance and also increase their self-regulation.